Psychology in Oceania and the Caribbean - Rich, Grant J.; Ramkumar, Neeta A. (Cham : Springer International Publishing : Imprint: Springer, 2022)
The Caribbean and Oceania are understudied areas from a psychological perspective, and this book is designed to fill that knowledge gap. In addition to diverse, rich cultural traditions and abundant economic opportunity for some, these regions also reflect the challenges of modernity, including crime, poverty, ethnic tensions, adaptations to climate change, and disparities in health, education, and access to care. With contributions from noted psychologists in the Caribbean and Oceania, as well as experts from around the globe, this book provides nuanced examination of significant psychological issues in nations such as Fiji, Guyana, Belize, Haiti, Jamaica, and more. Psychologists, psychiatrists, and other mental health professionals with an interest in this part of the world, will find this volume a rich resource, as will those generally interested in the relationship between culture and psychology. This book takes you on an outstanding journey of what is occurring in cultural psychology in the 21st century. It addresses the abundance of each nation through a transformational lens of current practices in psychology in Oceania and the Caribbean. I would absolutely recommend it to anyone interested in sailing the high seas connecting the present with the endless possibilities of those who dare to journey into the waters of a divine future."- Florence Denmark, Past-President, American Psychological Association "Chock full of expert knowledge and insights, Psychology in Oceania and the Caribbean is an indispensable resource for psychologists. A must-read that will expand your understanding of life in these regions and beyond! "- Pamela A. Hays, PhD, Author of Addressing Cultural Complexities in Practice "This is a breath-taking book in its coverage of the uniquely endowed psychology worlds of Oceania and the Caribbean. Now that Dr. Rich, Dr. Ramkumar, and colleagues have produced this awesome book volume on the cultural psychology of the rim water nations, I have a palpable sense of relief from their having addressed a huge gap in cultural psychology scholarship. This volume opens hitherto undreamed of opportunities for further studies on cultural practices in psychology in Oceania and the Caribbean!"- Elias Mpofu, PhD, DE.D, CRC, MAPS, Professor of Health Sciences at the University of North Texas, Honorary Professor of Health Sciences at the University of Sydney and Executive Board member of the Australian Psychological Society's Rehabilitation Psychology Interest Group "This book represents a vital exploration into the purpose and practice of Psychology in island nations. It is a welcome compilation of academic writings from sociocultural perspectives within Oceania and the Caribbean and serves as a landmark account of the unique forces shaping the development and evolution of Psychology in these states." - Gerard Hutchinson MD, Professor of Psychiatry, University of the West Indies, St Augustine, Trinidad and Tobago.
Preface -- 1.Psychology in Paradise: Perspectives from Oceania and the Caribbean: An Overview Chapter -- Section: Psychology in the South Pacific -- 2.Psychology in Polynesia -- 3.Psychology in Hawaii and American Samoa -- 4.Psychology in New Zealand -- 5. Psychology in Melanesia -- 6. Psychology in Fiji -- 7. Psychology in New Caledonia (France) -- 8.Psychology in Papua New Guinea -- 9. Psychology in Micronesia -- Section: Psychology in the Caribbean -- 10. Psychology in the French speaking Caribbean -- 11. Psychology in Haiti - Wismick Jean-Charles and Grant J. Rich -- 12. Psychology in the Dutch speaking Caribbean -- 13. Psychology in the Spanish speaking Caribbean -- 14. Psychology in Puerto Rico -- 15. Psychology in Cuba -- Psychology in the Dominican Republic -- 16. Psychology in the Barbados and the Eastern Caribbean -- 17.Psychology in Jamaica -- 18. Psychology in Guyana and Trinidad and Tobago -- 19. Psychology in Belize -- Section: Conclusion -- 20. Conclusion: Past, Present, and Future of Psychology in Paradise.
Keywords: Ethnopsychology; Social psychology; Clinical psychology; Cross-Cultural Psychology; Social Psychology; Clinical Psychology